Consequences of nonconformist behaviors in a continuous opinion model. (24th February 2016) - Vieira, Allan R; Anteneodo, Celia; Crokidakis, Nuno
Abstract: We investigate opinion formation in a kinetic exchange opinion model, where opinions are represented by numbers in the real interval [−1, 1] and agents are typified by the individual degree of conviction about the opinion that they support. Opinions evolve through pairwise interactions governed by competitive positive and negative couplings, that promote imitation and dissent, respectively. The model also contemplates another type of nonconformity such that agents can occasionally choose their opinions independently of the interactions with other agents. The steady states of the model as a function of the parameters that describe conviction, dissent and independence are analyzed, with particular emphasis on the emergence of extreme opinions. Then, we characterize the possible ordered and disordered phases and the occurrence or suppression of phase transitions that arise spontaneously due to the disorder introduced by the heterogeneity of the agents and/or their interactions.